Secagem em camada de espuma (foam-mat drying) da folha da couve manteiga (Brassica oleracea L.) - Silva, Quissi Alves da (2020)
The consumption of leaf cabbage (Brassica oleracea L.) is very common throughout the country. It is a vegetable originating from the Mediterranean that has dark green leaves, belongs to the botanical family of brassicas and is well recognized for its high nutritional value. Considering the current trends for nutritious and fast-prepared foods, their use in the dehydrated form is an interesting alternative to reduce losses and thus add value to the product. Based on this information, the objective of this work was to obtain the powder from the cabbage leaf through the foam-mat-drying method. The foam was obtained from the vegetable compound added by the additive Portogel® classified in the literature as an emulsifier and used widely in food formulations. The physical characterization of the foam was carried out by the analysis of stability, density, percentage of expansion and incorporation of air and physical-chemical analyzes (ATT content, pH and moisture percentage). Drying was carried out according to the complete factorial design of 2³ + 3 central points, with independent variables: concentration of foaming agent (3, 4 and 5%), stirring time (3, 4 and 5 minutes) and temperature drying (50, 60 and 70 ° C) and the influence of these variables on the process response variables (drying time and final drying humidity) and on the characterization of the obtained powder was evaluated through statistical analysis. With the kinetics data, drying curves were made, as well as curves for drying rates. The results showed a typical drying curve, represented by a long constant period followed by a short period of decreasing rate. It was also observed that with the increase in the drying temperature there was a reduction in the drying time. The highest drying rates were shown in the experiments at 70 ° C and the lowest rates at 50 ° C. Regarding the samples of the obtained powder, they presented an average humidity of 8.8% (b.u) and water activity in average of 0.504o, which favors the conservation and commercialization within the standards required by the legislation. The powder produced in the 11 experiments and in the lyophilization showed low solubility in water, with an average of 28.79% for the foam layer and for the lyophilized powder, 32.50%. For the physical-chemical characteristics (macronutrients) ashes, carbohydrates, proteins, lipids and bioactive compounds, the powders of the 11 experiments showed values that indicate that the foam layer drying process favored the concentration of nutrients. In the physical-chemical analyzes (ATT, pH, SST) the obtained values were superior to the values of the vegetal compound indicating that the addition of the emulsifier modified these characteristics and all lyophilized powder did not present significant differences for these parameters